Comparing Molecular Mechanisms in Solar NH(3) Production and Relations with CO(2) Reduction - Mallamace, Domenico (Int J Mol Sci, 2020)
Molecular mechanisms for N(2) fixation (solar NH(3)) and CO(2) conversion to C2+ products in enzymatic conversion (nitrogenase), electrocatalysis, metal complexes and plasma catalysis are analyzed and compared. It is evidenced that differently from what is present in thermal and plasma catalysis, the electrocatalytic path requires not only the direct coordination and hydrogenation of undissociated N(2) molecules, but it is necessary to realize features present in the nitrogenase mechanism. There is the need for (i) a multi-electron and -proton simultaneous transfer, not as sequential steps, (ii) forming bridging metal hydride species, (iii) generating intermediates stabilized by bridging multiple metal atoms and (iv) the capability of the same sites to be effective both in N(2) fixation and in CO(x) reduction to C2+ products. Only iron oxide/hydroxide stabilized at defective sites of nanocarbons was found to have these features. This comparison of the molecular mechanisms in solar NH(3) production and CO(2) reduction is proposed to be a source of inspiration to develop the next generation electrocatalysts to address the challenging transition to future sustainable energy and chemistry beyond fossil fuels.